A Multivariate Time‐Series Examination of Motor Carrier Safety Behaviors. Issue 4 (5th September 2017) - Miller, Jason W.
Abstract : Motor carriers' operational safety affects multiple stakeholders including truck drivers, motor carriers, insurance companies, shippers, and the general public. In this article, I devise and test theory regarding motor carriers' longitudinal performance for three classes of safety behaviors linked to carriers' accident rates—Unsafe Driving, Hours‐of‐Service Compliance, and Vehicle Maintenance—tracked by the Federal Motor Carrier Safety Administration as part of the Compliance, Safety, and Accountability (CSA) program. Specifically, I draw on core concepts from sociological agency theory and resource dependency theory to devise middle‐range theory that generates never‐before‐tested hypotheses regarding carriers' longitudinal safety performance for these classes of safety behaviors after the start of the CSA program. The hypothesized predictions are tested by fitting a series of multivariate latent curve models to four years of panel data for a random sample of 484 large, for‐hire motor carriers operating in the United States. The empirical findings corroborate the theoretical predictions and remain after robustness testing. These findings have important implications for scholars, motor carrier managers, procurers of motor carrier transportation services, and public policy makers.